The Plant Mitochondrial Carrier Family: Functional and Evolutionary Aspects - Haferkamp, Ilka; Schmitz-Esser, Stephan (Frontiers in Plant Science, 2012)
Mitochondria play a key role in respiration and energy production and are involved in multiple eukaryotic but also in several plant specific metabolic pathways. Solute carriers in the inner mitochondrial membrane connect the internal metabolism with that of the surrounding cell. Because of their common basic structure, these transport proteins affiliate to the mitochondrial carrier family (MCF). Generally, MCF proteins consist of six membrane-spanning helices, exhibit typical conserved domains and appear as homodimers in the native membrane. Although structurally related, MCF proteins catalyze the specific transport of various substrates, such as nucleotides, amino acids, dicarboxylates, cofactors, phosphate or H+. Recent investigations identified MCF proteins also in several other cellular compartments and therefore their localization and physiological function is not only restricted to mitochondria. MCF proteins are a characteristic feature of eukaryotes and bacterial genomes lack corresponding sequences. Therefore, the evolutionary origin of MCF proteins is most likely associated with the establishment of mitochondria. It is not clear whether the host cell, the symbiont or the chimerical organism invented the ancient MCF sequence. Here, we try to explain the establishment of different MCF proteins and focus on the characteristics of members from plants, in particular from Arabidopsis thaliana.